2016
DOI: 10.2209/tdcpublication.2016-0001
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Finger Length and Occlusal Vertical Dimension in Adult Sudanese Women

Abstract: The objective of this study was to investigate the correlation between the length of each of three fingers (the index finger, 2D; ring finger, 4D; and little finger, 5D) and the occlusal vertical dimension (OVD). If such a relationship were established, it would simplify and facilitate the prediction and reestablishment of the OVD in the construction of complete dentures. The correlation between the OVD and the length of 2D or 5D has already been investigated in a number of studies. However, to our knowledge, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
1
5
1
Order By: Relevance
“…19,20 The restoration of the vertical occlusal dimension must be in harmony with the facial dimensions without producing tensions on the patient's face or causing discomfort. In the present study the average VOD was 64.03±5.15mm; for Alhajj et al, 21 it was 65.93mm from point Sn to point Me.…”
Section: Resultssupporting
confidence: 40%
“…19,20 The restoration of the vertical occlusal dimension must be in harmony with the facial dimensions without producing tensions on the patient's face or causing discomfort. In the present study the average VOD was 64.03±5.15mm; for Alhajj et al, 21 it was 65.93mm from point Sn to point Me.…”
Section: Resultssupporting
confidence: 40%
“…Recently, it has been used in dentistry to predict the OVD. Thumb finger length, distance from tip of the thumb to tip of the index fingers, index finger length, ring finger length and little finger length have been measured and correlated to the distance from the septum of the nose to the base of the chin and the distance from tip of the nose and tip of the chin among different populations . Once these distances are determined, the OVD can be approximated.…”
Section: Post‐extraction Methodsmentioning
confidence: 99%
“…Research which was conducted by Alhajj NM et al (2016), showed that there was a correlation between VDO and the length of the ring finger with a value of r = 0.320. 25 The study proved that there was a correlation between VDO and the length of the ring finger. Therefore, the ring finger could be used as an alternative method for determining VDO.…”
Section: Discussionmentioning
confidence: 83%